2020
DOI: 10.1101/2020.04.27.049031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of kidney ureteric bud and collecting duct organoids that recapitulate kidney branching morphogenesis

Abstract: One sentence summary: Collecting duct organoids derived from primary mouse and human ureteric bud progenitor cells and human pluripotent stem cells provide an in vitro platform for genetic dissection of development, regeneration and diseases of the mammalian collecting system. Abstract:Kidney organoids model development and diseases of the nephron but not the contiguous epithelial network of the kidney's collecting duct (CD) system. Here, we report the generation of an expandable, 3D branching ureteric bud (UB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…These recent data suggest that increasingly complex and bioengineered culture systems are crucial to support and aid the development of a functional and mature nephron unit model. More recently, human fetal kidneys were utilised to isolate ureteric bud progenitor cells to finally establish optimal culture conditions for generating a renal organoid model derived from primary fetal samples (Zeng et al, 2021). Overall, this 3D in vitro system allowed a better understanding of kidney branching morphogenesis, as well as congenital defects.…”
Section: Kidneymentioning
confidence: 99%
“…These recent data suggest that increasingly complex and bioengineered culture systems are crucial to support and aid the development of a functional and mature nephron unit model. More recently, human fetal kidneys were utilised to isolate ureteric bud progenitor cells to finally establish optimal culture conditions for generating a renal organoid model derived from primary fetal samples (Zeng et al, 2021). Overall, this 3D in vitro system allowed a better understanding of kidney branching morphogenesis, as well as congenital defects.…”
Section: Kidneymentioning
confidence: 99%
“…These studies have revealed specific morphogens and cytokines that can drive the differentiation of PSCs towards a renal specification ex vivo (Takasato et al, 2014;Xia et al, 2014;Morizane et al, 2015;Takasato and ErPei, 2015;Taguchi and Nishinakamura, 2017;Uchimura et al, 2020). Collectively, procedures allowing the generation of organoids resembling separate components of the mammalian kidney have been established (Figure 1), including: nephron progenitor (NP), ureteric bud (UB) and even stromal progenitor (SP) organoids (Zeng et al, 2021;Palakkan et al, 2022;Tanigawa et al, 2022;Vanslambrouck et al, 2022).…”
Section: Human Pluripotent Stem Cells Derived Organoids: How To Model...mentioning
confidence: 99%
“…Briefly, Ret plays a crucial role in early UB induction and branching, among other roles, without which extreme phenotypes such as renal agenesis or prenatal fatality can be observed. Human PSC-derived UB organoids have been successfully used to mimic congenital anomalies resulting from mutations in RET, proving the feasibility of modelling such diseases by in vitro genetic editing and 3D culture (Zeng et al, 2021). In their study, the authors have Comparison of protocols for hPSC-derived kidney organoid differentiation.…”
Section: Human Pluripotent Stem Cells Derived Organoids: How To Model...mentioning
confidence: 99%
“…Overall, a 3D kidney organoid capable of mimicking the kidney formation from the UB progenitor to a more mature stage was established. [ 177 ] Furthermore, a protocol was developed for the differentiation of hESCs into kidney organoids. To accomplish this, a precise combination of growth factors was established to induce the ureteric bud and metanephric mesenchyme.…”
Section: Decm Hydrogels For Engineering Organoids/assembloids For Tis...mentioning
confidence: 99%
“…Reproduced under the terms of the Creative Commons Attribution CC BY license. [ 177 ] Copyright 2021, Zipeng Zeng et al. C) Representative images of DHE staining of ad‐MSCs cultured with and without ECM, in the hypoxia‐reoxygenation model in vitro.…”
Section: Decm Hydrogels For Engineering Organoids/assembloids For Tis...mentioning
confidence: 99%